2018
DOI: 10.1016/j.apsb.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Helioscopianoids A–Q, bioactive jatrophane diterpenoid esters from Euphorbia helioscopia

Abstract: The EtOH extracts of the whole plants of Euphorbia helioscopia afforded 17 new jatrophane diterpenoid esters, helioscopianoids A–Q (1—17), along with eight known compounds (18–25). Their structures were elucidated by extensive spectroscopic methods and Mo2(OAc)4-induced ECD analysis, and the structures of compounds 1, 2, and 7 were confirmed by X-ray crystallography. Compounds 1–17 were evaluated for inhibitory effects on P-glycoprotein (P-gp) in an adriamycin (ADM)-resistant human breast adenocarcinoma cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Besides, 220 could reduce rotenone-induced PC12 cell damage, and 173, 220, and 224 displayed neuroprotective activities against serum deprivation-induced PC12 cell damage. SAR studies and corresponding P-gp inhibitory effects demonstrated that the presence of different acyl groups or carbonyl groups at C-7 in the same jatrophane core, especially the butanoyl group instead of the hydroxy group at C-7, plays a significant role in their activity (Mai et al 2018b). Rédei et al (2018) isolated novel segetane diterpenoid 77, new jatrophane compound 279, along with two other known compounds, segetane 88 and jatrophane 448 from E. taurinensis.…”
Section: Mdr Reversing Activitymentioning
confidence: 99%
“…Besides, 220 could reduce rotenone-induced PC12 cell damage, and 173, 220, and 224 displayed neuroprotective activities against serum deprivation-induced PC12 cell damage. SAR studies and corresponding P-gp inhibitory effects demonstrated that the presence of different acyl groups or carbonyl groups at C-7 in the same jatrophane core, especially the butanoyl group instead of the hydroxy group at C-7, plays a significant role in their activity (Mai et al 2018b). Rédei et al (2018) isolated novel segetane diterpenoid 77, new jatrophane compound 279, along with two other known compounds, segetane 88 and jatrophane 448 from E. taurinensis.…”
Section: Mdr Reversing Activitymentioning
confidence: 99%
“…Helioscopianoid P and helioscopianoid H (Figure 2) are two jatrophane-type diterpenoids isolated from the whole plants of E. helioscopia , at 20 µM, exhibit inhibitory effects on P-glycoprotein in adriamycin (ADM)-resistant human breast adenocarcinoma cell line (MCF-7/ADR), while helioscopianoid L, helioscopianoid H and helioscopianoid B (Figure 2), also jatrophane-type diterpenoids isolated from the same species, exhibit neuroprotective effects against serum deprivation-induced PC12 cell damage and rotenone-induced PC12 cell damage [103].…”
Section: Other Biological Activity Of Euphorbia Plantsmentioning
confidence: 99%
“…Euphorbia helioscopia L., belonging to the genus Euphorbia (Euphorbiaceae), is an annual herb widely distributed in most parts of China and is used in traditional medicine to treat warts, bacillary dysentery, and tumors . In a previous chemical investigation, 1 novel jatropholane diterpenoid with a 5/6/7/7 fused-ring system, 4 unprecedented diterpenoids possessing 5/6/4/6 fused-ring and 7,8- seco -jatrophane skeletons, and 17 new jatrophane diterpenoids, together with 15 known jatrophane diterpenoids, were characterized in several fractions isolated from an EtOH extract of the whole plants . Some of these compounds showed antiviral (HSV-1), neuroprotective, and permeability glycoprotein (P-glycoprotein) inhibitory activities.…”
mentioning
confidence: 99%